Efficacy of pharmacologic therapies in patients with acute heart failure: A network meta-analysis - Dai, Hengheng; Li, Haisong; Wang, Bin; Zhang, Jingjing; Chen, Ying; Zhang, Xuecheng; Liu, Yan; Shang, Hongcai (Frontiers in Pharmacology, 2022)
Background: A network meta-analysis (NMA) of the current recommended drugs for the treatment of acute heart failure (AHF), was performed to compare the relative efficacy. Methods: We used PubMed, EMBASE, Cochrane Clinical Trials Register, and Web of Science systems to search studies of randomized controlled trials (RCT) for the treatment of AHF recommended by the guidelines and expert consensus until 1 December 2020. The primary outcome was all-cause mortality within 30 days. The secondary outcomes included 30-days all-cause rehospitalization, rates of HF-related rehospitalization, rates of adverse events, and rates of serious adverse events. A Bayesian NMA based on random effects model was performed. Results: After screening 14,888 citations, 23 RCTs (17,097 patients) were included, focusing on nesiritide, placebo, serelaxin, rhANP, omecamtiv mecarbil, tezosentan, KW-3902, conivaptan, tolvaptan, TRV027, chlorothiazide, metolazone, ularitide, relaxin, and rolofylline. Omecamtiv mecarbil had significantly lower all-cause mortality rates than the placebo (odds ratio 0.04, 0.01–0.22), rhANP (odds ratio 0.03, 0–0.40), serelaxin (odds ratio 0.05, 0.01–0.38), tezosentan (odds ratio 0.04, 0–0.22), tolvaptan (odds ratio 0.04, 0.01–0.30), and TRV027 (odds ratio 0.03, 0–0.36). No drug was superior to the other drugs for the secondary outcomes and safety outcomes. Conclusion: No drug was superior to the other drugs for the secondary outcomes and safety outcomes. Current drugs for AHF show similar efficacy and safety.